Te puedo ayudar? = Can I help? - Janovitz, Marilyn; Fernández, Queta (New York : North-South Books, 2008)
A little wolf's father gratefully accepts his son's offer to work with him in the garden, even though the cub is sometimes more of a hinderance than a help.
Spanish and English.
Keywords: Helpfulness; Gardening; Fathers and sons; Wolves; Spanish language materials -- Bilingual; Spanish language materials; Stories in rhyme; Juvenile literature; Juvenile fiction